Scheduling Preventive Maintenance on Auto Rooting Machine at Toys Manufacturer Company - Maukar, Anastasia Lidya; Sosodoro, Ineu Widaningsih; Adiprabowo, Rhiza (Universitas Katolik Parahyangan, 2016)
Maintenance cost becomes one of the problems that manufacturing company is facing nowadays due tolack of maintenance system. The main objective of this research is to reduce the maintenance cost on autorooting machine in toy manufacturer by developing a scheduled preventive maintenance. Data of machinebreakdowns and costs related to maintenance, components, and the interval time of failure for each machinewere collected. To develop a preventive maintenance system, the interval of component replacement must bedetermined. The minimum cost model is attained by finding the right interval time. The result of this researchshows that by implementing proposed maintenance schedule the machine reliability has 45% increase andmaintenance cost decreases by 48%.